P05.21 T1-flair to T1-gadolinium MRI ratio as a predictive value of treatment response in non-small-cell lung cancer (NSCLC) patients affected by multiple brain metastases. (19th September 2018) - Alemany, M; Domènech, M; Vilariño, N; Jové, M; Brao, I; Arellano, M; Lucas, A; Navarro, A; Palmero, R; Simó, M; Velasco, R; Nadal, E; et al.
Abstract: Background: Treatment strategies for multiple brain metastases (BM) are usually palliative, being whole brain radiation therapy (WBRT) the mainstay therapy so far. However, side effects such as cognitive decline, are not exempted. Systemic therapies as alternative treatment, although controversial, can be an alternative. To avoid WBRT adverse events and control both, extracranial and intracranial disease. Our purpose is to analyze the impact of peritumoral edema on the intracranial response to current systemic therapy. Material and Methods: A retrospective study including 28 patients, stage IV nonsquamous NSCLC with multiple BM (>3) treated with chemotherapy (CT)based on carboplatin plus pemetrexed (group A, n=18) or CT plus WBRT (group B, n=10) during the period 2014–2016. Patients received upfront CT if neurologic symptoms were absent or minor (using or not steroids). Intracranial response by RANO-BM criteria was correlated with the degree of BM-associated edema estimated by measuring the maximum diameter ratio among T1-Flair and T1-gadolinium (F/G) per each BM at the baseline MRI. Results: Median age was 55 (40–72) and most patients were men (71%), had smoking history (89%) and lung adenocarcinoma (89%). Only 1 patient harboured an EGFR mutation. Most patients had ECOG PS0-1 (96%) and 46% were off steroids. Median DS-GPA was 2 (1–4). The median follow-up was 11.6 months. No differences were observed in baseline characteristics among both groups, except for steroids doses that were higher in group B. Median OS was similar between group A and B (12.9 vs 10.9 months respectively, p=.317). Median F/G ratio was significantly higher in patients treated with WBRT compared with those treated with upfront CT (2.36 vs 1.58; p=.008). In patients treated with CT, F/G ratio was higher in those who developed intracranial progression to CT (2.60 ± 1.58) compared with those who achieved partial response or stable disease (1.32 ± 0.45 and 1.47 ± 0.45; p=.006). In patients treated with WBRT, F/G ratio was not predictive of response. Based on ROC analysis, a 2.1 cutoff on F/G ratio had a sensitivity of 71.4% and a specificity of 81.5% to identify the patients who benefited from upfront systemic treatment. Conclusion: Peritumoral edema measured by F/G ratio is associated with failure of systemic CT in NSCLC patients affected by multiple and asymptomatic BM at baseline. F/G ratio seems a promising tool to identify BM patients in whom WBRT can be delayed. A prospective validation is warranted.